2022
DOI: 10.1155/2022/7960559
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical History and Basic Science Origins of Transcutaneous Osseointegration for Amputees

Abstract: Transcutaneous osseointegration for amputees (TOFA) refers to an intramedullary metal endoprosthesis which passes transcutaneously to connect with a limb exoprosthesis. The first recognizably modern experiments and attempts occurred in the 1940s. Multiple researchers using a plethora of materials and techniques over the following 50 years identified principles and obstacles which informed the first long-term successful surgery in 1990. Unfortunately, the current mainstream TOFA literature presents almost exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…However, despite TOFA being used clinically to reconstruct lower extremity amputees for over 30 years ( Hoellwarth et al, 2022f ; Hoellwarth et al, 2020b ), only two human in vivo studies were identified reporting the effect on proximal femur bone density, both published in 2019. Hansen reported on 19 transfemoral amputees followed up to 30 months ( Hansen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite TOFA being used clinically to reconstruct lower extremity amputees for over 30 years ( Hoellwarth et al, 2022f ; Hoellwarth et al, 2020b ), only two human in vivo studies were identified reporting the effect on proximal femur bone density, both published in 2019. Hansen reported on 19 transfemoral amputees followed up to 30 months ( Hansen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcutaneous osseointegration for amputees (TOFA), recently reviewed ( Hoellwarth et al, 2020a ; Hoellwarth et al, 2022f ), is a surgical reconstruction technique wherein an intramedullary metal implant is anchored directly to the skeleton and then attached to a standard external prosthetic limb via a permanent transcutaneous connector. Versus TP, TOFA improves prosthetic use and quality of life ( Hagberg et al, 2008 ; Lundberg et al, 2011 ) without minimal associated risk of complications leading to proximal limb amputation or mortality ( Hoellwarth et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the basic and clinical sciences are still rapidly progressing. Recent articles [ 11 , 49 , 50 ] provide in-depth yet clinically oriented explorations of the historical origins, basic science progression, and clinical evolution. Some critical topics are worth highlighting here.…”
Section: Discussionmentioning
confidence: 99%
“…This process, termed osseointegration (OI), results in a bone-anchored prosthesis in which the implant that extends percutaneously, i.e., through the skin, allows a direct functional and structural connection to the prosthetic components ( 22 , 23 ). Bone-anchored implants have been used for dental and maxillofacial reconstructions for decades, and since the 1990s, they have been used for prosthetic reconstructions for individuals with transfemoral amputations ( 24 ). Bone-anchored prosthesis is a treatment option for various amputation levels in several areas worldwide.…”
Section: Introductionmentioning
confidence: 99%